A NOVEL TCHNOLOGY FOR HARMONICS AND UNBALANCE COMPENSATION IN ELECTRIC TRACTION SYSTEM USING DIRECT POWER CONTROL METHOD - Sushma V. Sangle; Prof. CH. Malla Reddy (International Journal of Innovations in Engineering Research and Technology, 2021)
Power quality problems in power systems have been improved due to nonlinear loads. To compensate these problems Direct Power Compensator was proposed in this paper. A Direct Power Compensator (DPC) is proposed in this paper to eliminate the harmonic currents, compensate power factor and voltage unbalance problems created by the nonlinear loads present in three phase systems. A DPC contains back to back converter by sharing the same dc link power and v/v transformer to provide a voltage balance in transmission line. Hysteresis harmonic current regulator is used to produce pulse for back to back converter. A controller maintains the dc-link voltage and compensates the power factor, harmonic currents. A comparative analysis for traction system with and without DPC was performed using MATLAB Simulink. Simulation results show the controller advantages and the applicability of the proposed method in railway systems.